2021
DOI: 10.1155/2021/8734615
|View full text |Cite
|
Sign up to set email alerts
|

Routine Medical Check-Up and Self-Treatment Practices among Community-Dwelling Living in a Mountainous Area of Northern Vietnam

Abstract: This study was conducted to evaluate the routine medical check-up and self-treatment behaviors of people living in a remote and mountainous setting in Northern Vietnam and identify their associations. A cross-sectional study was conducted on 175 people in August 2018 in Cao Son commune, Da Bac district, Hoa Binh. Information regarding routine medical check-ups and self-treatment behaviors was collected by using a structured questionnaire. Multivariate logistic regression was used to examine the associations. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 38 publications
1
6
1
Order By: Relevance
“…In contrast, people who live in rural areas depend more on pharmaceutical/ herbal treatment. This result is consistent with a study done in Vietnam, which shows that limited access to healthcare in mountainous areas has a rule in decreasing medical checkups and increasing dependency on self-treatment practice [20].…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, people who live in rural areas depend more on pharmaceutical/ herbal treatment. This result is consistent with a study done in Vietnam, which shows that limited access to healthcare in mountainous areas has a rule in decreasing medical checkups and increasing dependency on self-treatment practice [20].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, since health services are relatively away from residence and transport costs within these hilly regions are comparatively high, it was difficult to access health services among indigenous people who mostly rely on agriculture, cattle farming, and day labour [ 47 , 54 ]. Considering all these factors, indigenous people might prefer to self-medicate unless the medical condition was serious [ 47 , 55 ]. Several studies suggested that people often neglect their diseases and prefer to use self-prescribed medication instead of visiting a doctor and lack of knowledge and illiteracy influence their ignorance about health issues [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…DM patients who never had general medical check-ups were twice as likely to have low awareness of DM medication when compared with those who had had a general medical check-up. This might be because general medical check-ups provide health-related information, help identify issues early, assist in planning treatments as well as improve the awareness of medication ( 42 ).…”
Section: Discussionmentioning
confidence: 99%